Readiness For Community Re-Integration Among Victims of Community Violence: Prognostic Functions of Post-Traumatic Stress Disorder and Depression - Ojih, Emmanuel Eche; Gyang, Tony R. (NIU Journal of Social Sciences, 2026)
Community violence remains a significant public health concern with profound psychological and social consequences for affected individuals. This study examined the prognostic functions of posttraumatic stress disorder (PTSD) and depression on readiness for community reintegration among victims of community violence. The study adopted a cross-sectional survey design and was anchored on the Conservation of Resources Theory. A total of 368 participants were selected through a multistage sampling technique. Data were collected using standardized measures of PTSD, depression, and readiness for community reintegration. Descriptive statistics, multiple linear regression, and moderation analyses were employed for data analysis. The findings revealed that PTSD significantly and positively predicted readiness for community reintegration (β = .227, t = 4.296, p < .001), whereas depression did not significantly predict readiness for community reintegration (β = .079, t = 1.491, p = .137). Furthermore, depression did not significantly moderate the relationship between PTSD and readiness for community reintegration (β = -.002, t = -0.148, p = .882). These findings suggest that PTSD may be associated with increased motivation to reconnect with community resources and social support systems following traumatic experiences, while depression appears to have limited influence on reintegration readiness. The study concludes that trauma-related experiences play a significant role in shaping readiness for community reintegration among victims of community violence. It is recommended that trauma-informed interventions be integrated into community reintegration programmes to facilitate psychosocial recovery and sustainable reintegration outcomes. Keywords: Posttraumatic stress disorder, depression, community violence, readiness for community reintegration, psychosocial recovery, trauma survivors.